2007
DOI: 10.1002/pssr.200701253
|View full text |Cite
|
Sign up to set email alerts
|

First principle study of the cation vacancy in anatase TiO2

Abstract: Diluted magnetic semiconductors (DMS) [1] are a rapidly growing research field due to their potential applications in spintronic [2] devices. Several semiconducting oxide materials such as CaO [3], ZnO [4], HfO 2 [5], SnO 2 [6], TiO 2 [7] have been shown both experimentally and theoretically to have DMS properties. Normally there exists no magnetism in these material, but it will appear when defects exist. Introducing transition metal substitutions at the cation positions is one way to produce magnetism. Cu at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Several semiconducting oxide materials such as ZnO 3, HfO 2 4, SnO 2 5 have been shown to have DMS properties. Normally there exists no magnetism in semiconducting oxide materials, but it will appear when defects exist, such as transition metal (TM) substitutions at cation positions 3, 5, nonmetal atom doping at anion positions 6, or cation intrinsic vacancies 4, 7. As a common wide band semiconductor, TiO 2 has also been studied as a possible DMS material.…”
Section: Local Magnetic Moments (Ms) (μB/atom) Of Ti and O Atoms In Tmentioning
confidence: 99%
“…Several semiconducting oxide materials such as ZnO 3, HfO 2 4, SnO 2 5 have been shown to have DMS properties. Normally there exists no magnetism in semiconducting oxide materials, but it will appear when defects exist, such as transition metal (TM) substitutions at cation positions 3, 5, nonmetal atom doping at anion positions 6, or cation intrinsic vacancies 4, 7. As a common wide band semiconductor, TiO 2 has also been studied as a possible DMS material.…”
Section: Local Magnetic Moments (Ms) (μB/atom) Of Ti and O Atoms In Tmentioning
confidence: 99%
“…Both oxygen vacancy and titanium vacancy were proposed to be responsible for the ferromagnetism. On one hand, theoretical studies indicated that the cation vacancy or divacancy are ferromagnetically coupled, 13,14 similar to the case of undoped HfO 2 . 6 But on the other hand, more and more experimental evidences show that the magnetic property of undoped TiO 2 is strongly related to oxygen vacancy, and thus it was thought to be the source of room-temperature ferromagnetism in undoped semiconducting or insulating oxides.…”
mentioning
confidence: 94%
“…Similar to the case of HfO 2 6 and CaO 26 , the presence of cation vacancy causes a clear spin split in the valence band, and a total magnetic moment of 4.0 μ B was produced, mainly contributed by the six adjacent oxygen ions around the titanium vacancy which is consistent with results of previous calculations based on LSDA or GGA functional. 13,14 Further calculations were carried out to assess the relative stability of the ferromagnetic and antiferromagnetic alignments between the magnetic moments localized on different titanium vacancies using the 96-atom 2 × 2 × 2 supercell where the distance between two titanium vacancies is 7.6 Å, and the FM state is found to be more stable than the AFM state by 112 meV, indicating a substantially long-range ferromagnetic ordering of cation vacancy induced by local magnetic moments in titanium-deficient TiO 2 . As a result, it is proposed that the carriers, i.e., holes from the p orbitals of these oxygen ions, are thought to 8 induce the long-range ferromagnetism, and similar ferromagnetically coupled state is also expected in other cation-deficient semiconductors such as In 2 O 3 , SnO 2 , and CdS.…”
mentioning
confidence: 99%
“…The experimental results suggest that the observed FM comes from oxygen vacancies for oxides HfO 2 , TiO 2 , In 2 O 3 and SnO 2 [1][2][3][4][5], but from cation vacancies for MgO [6,7]. Most of ab initio calculations demonstrate that cation vacancies are responsible for the magnetic moments in undoped oxides such as HfO 2 , TiO 2 , ZnO, SnO 2 , ZrO 2 and MgO [8][9][10][11][12][13][14][15][16]. Ferromagnetism could also be produced by doping non-magnetic sp elements such as C, N, Mg and Al in oxides, nitrides and sulfides [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 84%